Measuring Quality Performance in Construction - Sodangi, Mahmoud; Idrus, Arazi; Khamidi, M. Faris (2010)
A strong quality culture has been recognized to be an important prerequisite to the achievement of sustained competitive advantage through the continuous delivery of high quality products and services as well as clients’/end-users’ satisfaction. Today, the construction industry is one with poor quality emphasis compared to other sectors like the manufacturing and service sectors. Many criticisms have been directed to the industry for generally poor workmanship. It is not only the final product that is subjected to criticisms but the processes and parties involved are under high pressure for better quality in construction. This paper is in two parts; the first part reviews the concept of quality performance in construction projects and while the second part presents a study conducted to compare clients’ evaluation of the quality performance of government and private contractors around Selangor and Johor states with the aim of finding the category of contractors that has better quality performance at the project-level. To this regard, a field survey was conducted. Structured questionnaires were used to collect data. The data collected were analyzed to determine the ranking and test of difference in quality performance between the two categories of contractors using Mean Item Score and t-test respectively. It was found out that clients consider the quality performance of private contractors to be better than that of government contractors.